Pengaruh Kombinasi Pupuk Kascing dan NPK Phonska Terhadap Ketersdiaan Hara Nitrogen dan Hasil Selada pada Inceptisol di Lahan Kering Pulau Timor - Peters Bako; Antonius S. J. Adu Tae; Moresi M. Airtur; Diana Y. L. Serangmo; Lorenso J. E. S. Taopan (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Lettuce cultivation on Inceptisol in the drylands of Timor Island is constrained by low nutrient availability, especially nitrogen. The application of vermicompost fertilizer combined with NPK Phonska fertilizer is expected to increase the availability of N and lettuce yields through proper dosage settings. This study aims to obtain a combination dose of vermicompost and NPK Phonska fertilizer that gives the best effect on the availability of N and lettuce yield on Inceptisol in drylands of Timor Island. The research was designed in a single factor experiment using a completely randomized design. The treatments tested were the doses of combined vermicompost and NPK phonska fertilizers, namely: control/no fertilizer application (P0); 20t.ha-1 vermicompost + 200kg.ha-1 NPK phonska (P1), 20t.ha-1 vermicompost + 400kg.ha-1 NPK phonska (P2); 30t. ha-1 landfill + 200kg.ha-1 NPK phonska (P3); 30t.ha-1 landfill + 400kg.ha-1 NPK phonska (P4); 40t.ha-1 landfill + 200kg.ha-1 NPK phonska (P5); and 40t.ha-1 landfill + 400kg.ha-1 NPK phonska (P6). Each treatment was made in 3 replications so that 21 experimental units were obtained. The results showed that: (1) all treatments of combined doses of vermicompost and NPK Phonska fertilizers gave values of soil N-total content and plant tissue N that were significantly different from the control treatment, but no significant differences were found between the doses of combined vermicompost and NPK Phonska fertilizers; (2) the treatment of 40t.ha-1 vermicompost + 400kg.ha-1 NPK Phonska produced the highest fresh weight per lettuce plant which was not significantly different from the treatment of 40t.ha-1 vermicompost + 200kg.ha-1 NPK Phonska but significantly different from all other treatments. There was no best combination dose treatment of vermicompost and NPK Phonska fertilizer in this study.